2002
DOI: 10.1034/j.1399-0012.2002.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis infection and laboratory diagnosis in solid‐organ transplant recipients

Abstract: Tuberculosis (TB) is an unusual infection in transplant recipients. We evaluated (i) the frequency of TB, (ii) the duration to develop the TB infection, and (iii) clinical consequences, in 380 solid-organ recipients from January 1995 to December 2000. A total of 10 (2.63%) patients (eight renal, two liver transplant recipients) were found to have post-transplantation TB. The frequency of TB in this patient population is 8.5-fold higher than the prevalance in the general Turkish population. Tuberculosis develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 4 publications
4
46
1
Order By: Relevance
“…Primary infection in renal transplant patients is rare and occurs commonly as a result of transmission by donor kidney. 4 In our study, the prevalence of TB was 2.8% owing to the high frequency of TB in general Turkish population, and 44% of the patients developed TB within 1 year after transplantation that may be due to reactivation of latent infection. Ergun et al 6 reported the prevalence as 3.5% in their study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary infection in renal transplant patients is rare and occurs commonly as a result of transmission by donor kidney. 4 In our study, the prevalence of TB was 2.8% owing to the high frequency of TB in general Turkish population, and 44% of the patients developed TB within 1 year after transplantation that may be due to reactivation of latent infection. Ergun et al 6 reported the prevalence as 3.5% in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The risk is mainly determined by endemicity of the infection in specific geographic area. Cavusoglu et al 4 reported that TB prevalence after solid organ transplantations was 2.63%, which was 8.5-fold higher than the prevalence in the general Turkish population (0.3%). The rate of occurrence of M. tuberculosis infection according to data from WHO was estimated to be 45/100,000 in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this patient population, TB has been associated with graft dysfunction and increased mortality rates. [4][5][6] Not only the overall immunosuppression, but also older age and coexisting diseases such as diabetes, chronic liver disease, and co-infections have been associated with predisposition to TB. 7 TB can be frequently pulmonary, but extrapulmonary involvement is not rare, affecting 16% of the transplant patients.…”
Section: Introductionmentioning
confidence: 99%